KRAS/NRAS/BRAF Mutations as Potential Targets in Multiple Myeloma - Pasca, Sergiu; Tomuleasa, Ciprian; Teodorescu, Patric; Ghiaur, Gabriel; Dima, Delia; Moisoiu, Vlad; Berce, Cristian; Stefan, Cristina; Ciechanover, Aaron; Einsele, Herman (Frontiers in Oncology, 2019)
In multiple myeloma the mutational profile is mainly represented by translocations involving chromosome 14 and by single nucleotide mutations, frequently involving genes implicated in the mitogen activated protein kinase (MAPK) pathway, as KRAS, NRAS, and, less frequently, BRAF. Because KRAS/NRAS/BRAF mutations are associated with a higher number of mutations per patient, we hypothesize that this group of patients could benefit from therapy with checkpoint inhibitors because of the higher frequency of neo-antigens that this group would present. This might also true for IMiD therapy, because of their activatory effect on T cells. Because, KRAS/NRAS/BRAF are members of the MAPK pathway, this subgroup of patients would also benefit from inhibitors of MAPK, either directly on the specific mutation or through downstream targeting of MEK1/2 or ERK1/2 to account for a possible compensatory collateral signaling that might activate as response to upstream inhibition.